2019
DOI: 10.1016/j.molcel.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Acetylation of PHF5A Modulates Stress Responses and Colorectal Carcinogenesis through Alternative Splicing-Mediated Upregulation of KDM3A

Abstract: Highlights d Quantitative acetylomics reveals hyperacetylated proteins upon nutrition starvation d Multiple cellular stresses result in p300-dependent PHF5A K29 acetylation d PHF5A K29 acetylation enhances KDM3A expression by stabilizing its mRNA d PHF5A acetylation and KDM3A upregulation predict poor prognosis in colon cancer

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 41 publications
3
62
0
Order By: Relevance
“…Many studies have reported that histone demethylases were upregulated in human cancers (11,(33)(34)(35). However, it is still unclear whether this is a bystander event or a driver of tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that histone demethylases were upregulated in human cancers (11,(33)(34)(35). However, it is still unclear whether this is a bystander event or a driver of tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Seven genes (ACO2, FOXD1, LMAN2, PHF5A, PRR7, PRR7-AS1, and SKAP2) were implicated in both HNs and colonoids; FOXD1, PRR7, and SKAP2 encode proteins with known roles in immune regulation, [50][51][52] and PHF5A mediates stress resistance in a model of colorectal cancer. 53…”
Section: Q22mentioning
confidence: 99%
“…Recently, one study reported that SF3b7 is acetylated mainly at its Lys29 residue under nutrient starvation [79]. The study further found that this modification enhances the interaction between SF3b7 and other SF3b components and changes the cellular pre-mRNA splicing patterns.…”
Section: Modifications Of Sf3bmentioning
confidence: 83%
“…The SF3b complex appears like a flaming torch with SF3b1 on the upper flame part, SF3b3 on the lower torch part and other subunits dotted within or around. The modification-related residues of SF3b1 (Thr434), SF3b2 (Arg508), and SF3b7 (Lys29) are indicated with red circles and colored in black [73,78,79]. The right panel shows three views of the SF3b complex in surface mode.…”
Section: Introductionmentioning
confidence: 99%